Improving image denoising methods for PDF image files - Jeevarekha, Gunasegran
The field of image processing is one which is highly researched for that one algorithm which can perform the best in all conditions. The restoration of historical documents is one branch of the field whereby there are many existing documents in degraded conditions which need restoration. These documents are contaminated with salt-and-pepper noise which occurs during scanning of the documents into PDF format files. The project look into finding the best algorithm that can denoise the PDF files and improve the appearance of the image files. Two algorithms are implemented and tested and a new algorithm is proposed for this purpose. The proposed algorithm produces promising results which are visually perceptual. Future works can focus on testing the new algorithm on other historical documents.